1984
DOI: 10.1002/bjs.1800711023
|View full text |Cite
|
Sign up to set email alerts
|

The localization of human breast carcinomas by radiolabelled monoclonal antibodies

Abstract: Immune-deprived mice bearing HX99 human breast carcinoma xenografts were injected with a radiolabelled monoclonal antibody, LICR-LON-M8 (M8), to investigate the dependence of tumour localization on (i) tumour site and (ii) antibody radiolabel. No significant difference was found in the degree of localization of radio-iodinated M8 in subcutaneous, renal or intracranial xenografts, but a highly significant improvement in HX99 localization by M8 was recorded using an 111indium-DTPA conjugate of the antibody (111I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1986
1986
1991
1991

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…With antibodies labelled with charged metallic ions such as Indium-111 ["'In] using a chelating agent (usually diethylene triamine pentacetic acid (DTPA)), unstable non specific protein binding may be a major factor in the background uptake of radioactivity (Hnatowich & McGann, 1987). This problem is most evident with the liver which may accumulate 30-40% of the injected radioactivity (Rainsbury, 1984). The pretreatment of "'In labelled antibodies with metal chelating agents has been shown in tissue culture to reduce the uptake of radioactivity by hepatocytes and may, therefore, improve the results of immunoscintigraphy (Davidson et al, 1990).…”
mentioning
confidence: 99%
“…With antibodies labelled with charged metallic ions such as Indium-111 ["'In] using a chelating agent (usually diethylene triamine pentacetic acid (DTPA)), unstable non specific protein binding may be a major factor in the background uptake of radioactivity (Hnatowich & McGann, 1987). This problem is most evident with the liver which may accumulate 30-40% of the injected radioactivity (Rainsbury, 1984). The pretreatment of "'In labelled antibodies with metal chelating agents has been shown in tissue culture to reduce the uptake of radioactivity by hepatocytes and may, therefore, improve the results of immunoscintigraphy (Davidson et al, 1990).…”
mentioning
confidence: 99%
“…Several investigators have reported successful radioimmunolocalisation of breast cancer (Colcher et al, 1983;Rainsbury, 1984;Kalofonos et al, 1988b), but limitations of this approach are the low absolute amount of antibody reaching the target (Epenetos et al, 1986), the heterogeneity of antigenic expression in tumour cells affecting antibody binding (Buchegger et al, 1983) and the persistence of high levels of blood pool radioactivity which makes tumour radioimmunodetection difficult. Several methods have been reported to reduce the blood pool activity.…”
mentioning
confidence: 99%
“…The amount accumulated, however, is so low that detectable contrast from normal tissues cannot be reliably achieved by external scanning. Attempts to increase the tumour to normal tissue contrast have evaluated different isotopes (Fairweather et al, 1983b;Rainsbury, 1984) and different methods of scanning such as emission tomography (Berche et al, 1982). These techniques, however, are methods of improving the sensitivity of the detection of the very small amounts of labelled antibody accumulated by tumours.…”
Section: Discussionmentioning
confidence: 99%